The effect of some non- fungal pesticides and certain chemicals in the growth of two pathogenic fungi isolated from the seeds and roots of the plant wheat - Samir Saadoon, Abdul amir; Jasim Shabani, Muhanad (Al-Qadisiyah Journal of Pure Science, 2018)
The study included the effect of two types of pesticides which pesticide jungles Algranstar and pesticide Insects alwide and two chemical compounds ( urea and sodium chloride) in some pathogenic fungi isolated from the seeds of varieties of wheat is July 2 certified 1 allocated to agriculture and collected from stores company Mesopotamia public / Branch Diwaniyah and compare pesticide alsa. . The results showed a difference morale of these transactions when used in three concentrations are 5. 10 , 15 mg / ml for vehicles chemicals and concentrations of.5 ,10, 15 mg / 10 mL of pesticides in seed germination soils sterile and non- sterile and growth radiography as well as in transactions overlap between the transactions in the soil seeds germination and the radial growth of Aftran testers Fusarium.oxysporum, Alternaria. tenuissima, and was the most influential transactions in fungi pesticide Algranstar the treatment followed by treatment pesticide Alwide and urea and sodium chloride compared with the transactions and transactions comparison of pesticide and mildew alsa. . It emerged from research show that the use of urea and sodium chloride in the treatment of wheat seed has a negative impact in some kinds of pathogenic fungi and its accompanying well as the use of pesticides Other fungal pesticide jungles Algranstar and insecticide Alwide adversely affect also the vitality and activity of fungi nurses and must therefore put the use of such pesticides in special programs to combat endemic pathogenic fungi in the soil and reduce the use of fungicides to less extent possible.. Also result showed significant difference in the coefficients overlap transactions single and mixed results overlap when using urea and sodium chloride with pesticide jungles Algranstar and insecticide Wide , which is considered as a way within the program to control the pathogenic fungi and The possibility of used as substitutes for fungicides in environments that suffer from insect pests and bushes comparing them with a control transactions and transactions comparison of pesticide and mildew Alalsa . It was found that some transactions have affected the activity and vitality of fungi nurses Fusarium oxysporum, Alternaria. Tenuissima.